Herbal Extract Mixture Modulates Intestinal Antioxidative Capacity and Microbiota in Weaning Piglets - Wang, Meiwei; Huang, Huijun; Wang, Lei; Yang, Huansheng; He, Shengwen; Liu, Feng; Tu, Qiang; He, Shanping (Frontiers in Microbiology, 2021)
Recently, herbal extracts have been applied in multiple aspects, such as medicine and animal feed. Different compositions of herbal extract mixture (HEM) have various components and diverse functions. This study aimed to evaluate the effects of HEM (Lonicera japonica, Astragalus membranaceus, Eucommia folium, and Codonopsis pilosula) on intestinal antioxidant capacity and colonic microbiota in weaned pigs. A total of 18 piglets [Duroc × (Landrace × Yorkshire)] with the initial body weight of 5.99 ± 0.13 kg (weaned at 21 days) were randomly divided into two groups (n = 9): the control group (CON, basal diet) and the HEM treatment group (HEM, 1,000 mg/kg HEM + basal diet). The experiment period lasted for 14 days. Our results showed that dietary supplementation with HEM modulated the antioxidant capacity through decreasing the activity of superoxide dismutase (SOD) in the ileum and glutathione peroxidase (GSH-PX) in the serum, and decreasing the mRNA expression of Kelch like-ECH-associated protein 1 (Keap1) in the jejunum and the protein level of Keap1 in the ileum. Moreover, the HEM group modified the composition of colonic microbiota with affecting relative abundances of the Firmicutes and Bacteroidetes at the phylum level. Taken together, supplementation of HEM can regulate the antioxidant capacity and modify the composition of colonic bacteria in weaning piglets. This study provides new insights into the combination effects of herbal extracts on weaning piglets.